On the hysteretic behavior of trapezoidally corrugated steel shear walls. (7th June 2012) - Emami, Fereshteh; Mofid, Massood
SUMMARY At present, corrugated plates have numerous applications such as web of plate girders and aerospace applications. Higher out‐of‐plane stiffness and initial elastic strength of the corrugated plates compared with flat plates are reasons for consideration. This study investigates the behavior of trapezoidally corrugated steel plate shear walls (TCSPSWs) under monotonic and cyclic loadings. Finite element analyses that include both material and geometric nonlinearities are employed for the examination. The results from finite element analysis are verified through tested specimen findings. Moreover, the behavior of the steel shear walls with the flat infill panels and the corrugated plate infill panels is compared. The results show that explicit dynamic analysis is the most suitable analysis for the TCSPSWs under quasi‐static loading. Furthermore, although strength of the TCSPSWs obtained from the finite element analysis and the test are fully coincident in elastic region, nonetheless, they are fairly coincident in elastic–plastic and plastic region. Copyright © 2012 John Wiley & Sons, Ltd.